The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.35891/jsb.v5i2.1585
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Relational Benefits Terhadap Kepuasan dan Loyalitas Nasabah

Abstract: English The purpose of this study was to determine the extent of the effect of relational benefitson satisfaction and loyalty on customers of the sharia Mandiri bank in Pasuruan City. The population of this study is the customers of the Mandiri Syari'ah bank.The sampling technique waspurposive sampling. The sample used was 100 customers of the Mandiri Syari'ah Bank. The analysis method used is path analysis. The results showed that the social benefits had a positive and significant effect on satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Also, the empirical evidence indicates that confidence benefits impact customer trust, and social benefits impact customer commitment. These results support other empirical studies (Dandis et al ., 2022c; Fatikhaturrohmah et al ., 2020; Fatima and Mascio, 2020; Wong et al ., 2019; Chou and Chen, 2018; Yang et al ., 2017; Dagger and Brien, 2010; Kim and Ok, 2009) that find significant connections between relationship marketing outcomes and the above variables.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the empirical evidence indicates that confidence benefits impact customer trust, and social benefits impact customer commitment. These results support other empirical studies (Dandis et al ., 2022c; Fatikhaturrohmah et al ., 2020; Fatima and Mascio, 2020; Wong et al ., 2019; Chou and Chen, 2018; Yang et al ., 2017; Dagger and Brien, 2010; Kim and Ok, 2009) that find significant connections between relationship marketing outcomes and the above variables.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Dandis et al (2022c) also observed that special treatment benefits had a significant positive impact on customer commitment and satisfaction. Moreover, Fatikhaturrohmah et al (2020) indicated that these benefits had a significant influence on the trust and satisfaction of customers. Kim and Ok (2009) also reported that benefits of this nature had a direct and indirect impact on affective commitment in the hospitality industry.…”
Section: Special Treatment Benefits Customer Satisfaction Commitment ...mentioning
confidence: 99%
See 2 more Smart Citations